2009
DOI: 10.1080/00379271.2009.10697589
|View full text |Cite
|
Sign up to set email alerts
|

Immature stages and nest construction inSynapsis yunnanus(Coleoptera: Scarabaeidae)

Abstract: In this paper we describe and illustrate the nesting behaviour, egg and larvae of all three instars of Synapsis yunnanus Arrow 1933. Two nests of S. yunnanus were observed in Northern Yunnan, China. The nest is subterranean and paracoprid, with female present in the nest chamber after oviposition. The brood ball is covered with a compacted layer of soil, and the egg chamber is proximal, situated in dung. Six brood balls were found in each nest. Larvae are compared with the only other species known in larval st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These have been called hatching spines, oviruptors, or egg-busters (Hayes, 1929). With the aid of muscular contractions, the egg-busters assist the embryo to break the chorion during the hatching process (Vitner & Král, 2009). Besides the function of egg-busters, some authors showed that the structure is also useful to identify some first-instar Coleoptera larvae (e.g., Scarabaeidae, Emden, 1941;Šípek et al, 2008).…”
Section: Key To Third Instar Of Orphninae Known Larvaementioning
confidence: 99%
See 2 more Smart Citations
“…These have been called hatching spines, oviruptors, or egg-busters (Hayes, 1929). With the aid of muscular contractions, the egg-busters assist the embryo to break the chorion during the hatching process (Vitner & Král, 2009). Besides the function of egg-busters, some authors showed that the structure is also useful to identify some first-instar Coleoptera larvae (e.g., Scarabaeidae, Emden, 1941;Šípek et al, 2008).…”
Section: Key To Third Instar Of Orphninae Known Larvaementioning
confidence: 99%
“…Gardner (1935) found egg-busters in Rutelinae (Anomala polita Blanchard, 1851) and Cetoniinae (Heterorrhina elegans (Fabricius, 1781) and Oxycetonia albopunctata (Fabricius, 1798)), but Fidler (1936) did not find this structure in Melolonthinae (Amphimallon solstitialis (Linnaeus, 1758), Melolontha melolontha (Linnaeus, 1758), and Serica brunnea (Linnaeus, 1758)). Vitner & Král (2009) in a study of immatures of Synapsis yunnanus Arrow, 1933 (Scarabaeinae) suggested that egg-busters may not always be responsible for the initial fracture of chorion and that these sclerites possibly have a supportive function. The authors noted that the egg-busters probably serve as mechanoreceptors, since the sclerotized insertions of setae of the egg-busters keep them in a constant position relative to the chorion.…”
Section: Key To Third Instar Of Orphninae Known Larvaementioning
confidence: 99%
See 1 more Smart Citation